A rare case of fungal meningitis with atypical presentation in immunocompetent patient - Kumar, Rajnish; ., Priyanka (International Journal of Research in Medical Sciences, 2018)
Fungal meningis is uncommon in general population especially in immunocompetent indivisuals. Meningitis, when caused by the fungal mycoses Cryptococcus neoformans, is normally seen in immunocompromised hosts. However, it is also seen in immunocompetent patients. In patients with an intact immune system, CM usually presents with the typical signs and symptoms of meningitis: fever, stiff neck, dizziness and headache. We report a rare case of fungal meningitis in a immunocompetent patient on antiseizure drugs for last 12 years misdiagnosed as phynetoin toxicity.